Body size determination in insects: a review and synthesis of size- and brain-dependent and independent mechanisms. - Callier, V.; Nijhout, H.F. (Biological Reviews of the Cambridge Philosophical Society, 2013)
Body size determination requires a mechanism for sensing size and a mechanism for linking size information to the termination of growth. Although the hormonal mechanisms that terminate growth are well elucidated, the mechanisms by which a body senses its own size are only partially understood; most of this understanding has come from the study of the mechanisms that control insect moulting and metamorphosis. We first review and discuss advances in our understanding of the physiological mechanisms by which insect larvae sense their size. Second, we present new findings on how larvae in which the size-sensing mechanism has been disrupted eventually terminate growth (in a size-independent manner). We synthesize recent insights into the genetic and molecular mechanisms of ecdysteroid regulation in Drosophila melanogaster with developmental physiology findings in Manduca sexta, paving the way for an integrated understanding of the mechanisms of body size regulation.